The Effect Of Leadership Effectiveness On Organizational Performance - Leonita Siwiyanti; Muhammad Khairul Amal; Ade Sudarma (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose – this paper seeks to examine the effect of leadership effectiveness on organizational performance. By looking at the Muhammadiyah organization in Indonesia, especially in Sukabumi. Methodology/approach - this research uses a quantitative method approach. The population of this research is all members of Muhammadiyah in Sukabumi. The sampling technique that will be used in this study is the random sampling method. Analysis of the data used is multiple linear regression analysis. Findings – it is found that simultaneously the three variables have a significant influence on (Y), which means the organization can develop if the leader applies leadership which includes Leader-Subordinate Relations, Task Structure and Leadership Position Strength simultaneously (simultaneously). And the leadership-subordinate relationship variable partially does not have a significant effect. While the other two variables have a significant effect. Novelty/value – leadership style or leadership model is often used as material for studies related to human resources, usually associated with employee performance, motivation and organizational behavior. While the organizational performance is very minimally studied, even though the development factor of an organization can be influenced by leadership.